Microbial insecticides for grape leaf folder control - F Jensen; M Aliniazee (California Agriculture, 1972)
The grape leaf folder, Desmia funeralis (Hbn.) Pyralidae: Lepidoptera, requires treatment every year in some Tulare County vineyards. The amount treated varies from a few acres to perhaps a third of the total acreage in the peak years. Although carbaryl (Sevin) gives excellent control, it causes disruptions of natural control factors under some conditions. In an effort to find more innocuous controls, many preparations of Bacillus thuringiensis Berliner have been tested against grape leaf folder over the last 13 years. The new high potency strain of Bt gives promise of highly effective control. This strain, known as HD-1, was isolated by the U.S.D.A.